Review of Hospitalization Rates Using Activity Based Costing Method at Rumah Sakit PKU Muhammadiyah Mamajang in Makassar Area - Sakia Putri Samsul; Muh. Rum; Asriani Hasan (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
The reason for this research is to decide whether the tax for ongoing administration at Rumah Sakit PKU Muhammadiyah Mamajang, Makassar Area, is appropriate when compared to the principle of bookkeeping prices in determining the unit cost of emergency clinical administration. The strategy used in this exam was quantitative with a spell binding methodology. Quantitative involvement is an assortment of information into numbers which then, at that point, break down the results. The type of information used in this study was essential information and additional information with information gathering techniques, especially perceptions and documentation. The results of this review showed that from the estimation of the use of activity based costing techniques for the VIP room it is Rp. 1,438,427, for Room I it is Rp. 1,407,446, for Room II Rp. 1,249,609 and for Room III Rp. 1,093,151. Calculation of current payments using movement based costing techniques, when compared to the strategy implemented by Rumah Sakit PKU Muhammadiyah Mamajang, the price of administrative fees can be lowered so as to provide lower results. This is because the expense assignment above for each item is unique.